A simplification of reading fluid properties using Microsoft Excel - Mohd Asri, Ibrahim (2012)
This project deals with simplification reading fluid properties using Microsoft Excel. The objective of this project to develop an excel file to easily obtain fluid properties without manual reading from table. The types of fluid are saturated water, saturated refrigerant-134a, saturated ammonia, saturated propane and air at 1 atm pressure while the fluid properties are density, dynamic viscosity, kinematic viscosity and friction factor. The formula in Microsoft Excel, INDEX, MATCH, INDIRECT, IF, AND, ISBLANK, NA and DROPDDOWLIST are used to build a combine formula that can obtain fluid properties from property tables. The combined formula was constructed step by step starting the listed value, followed by listed and unlisted value for SI units only and then the listed and unlisted value for SI units and English units in the property tables. Finally, one more combined formula was constructed to obtain friction factor based on Colebrook equation by using bisection method to solve that equation. Validation results were conducted where compared the results from manual reading and excel file. The error from both results was observed where all the error results are below 5 % and can be accepted. The different results from manual reading and excel file only occur for result in value decimal places. It can be comprehend that, to obtain fluid properties from property tables can be using Microsoft Excel by constructed a excel file. The developed excel file for future work is highly recommended for adding more properties, more type of fluid and using Visual Basic for Applications for advance editing.